Effect of employee selection and work placement on employee work achievement at PT Kereta Api Indonesia DAOP 1 Jakarta - Nikmah, Wasilatun; Armaniah, Henny (Journal of Economics and Business Letters, 2021)
Inappropriate selection and placement of employees will result in employee performance not being achieved optimally. Companies must pay more attention to recruitment and placement of employees properly and correctly, according to company needs. The purpose of this study was to determine whether selection has a significant effect on employee performance at PT Kereta Api Indonesia (Persero) DAOP 1 Jakarta, and whether employee placement has a significant effect on employee performance at PT Kereta Api Indonesia (Persero) DAOP 1 Jakarta. In this study, data were collected through interviews and questionnaires to 100 employees of PT Kereta Api Indonesia (Persero) DAOP 1 Jakarta with a quantitative approach and using a random sampling technique for sampling. The data analysis techniques used include validity and reliability tests, classical assumption tests using the Ordinary least squares (OLS) method, hypothesis testing through F-tests and t-tests as well as multiple linear correlation tests (R) and coefficient of determination (R²). ) with the help of software SPSS 21.0 For windows. Based on the results of research that has been carried out, the results of the t-test on the recruitment variable are 5.793, greater than the t-table (5.795 > 1.660) and the significance is less than 0.5, namely (0.000 > 0.05). So it can be concluded that there is a positive and significant effect of selection on employee performance at PT Kereta Api Indonesia (Persero) DAOP 1 Jakarta, and the results of the t-test on the employee placement variable are 3,490, greater than the t-table, namely (3,490 > 1,660) and the significance is less than 0.5, namely (0.001 > 0.05). so it can be concluded that there is a positive and significant effect of employee placement on employee performance at employees of PT Kereta Api Indonesia (Persero) DAOP 1 Jakarta.